Analysis, research and assessment of the measures of railway protection from snow - Gailienė, Inesa (International Conference “Environmental Engineering”, 2017)
The research object of this paper are the railway switches. The paper studies the efficiency of the usage system of a stationary switch protection in the Lithuanian railways. The study consisted of observations and condition assessment, as well as a survey of the people whose work is directly related to the switch exploitation, in order to establish the specifics, advantages, disadvantages, and experience in the Lithuanian railway system. It was found that the system is an efficient technical solution to obtain maximum results with minimal costs because the system is efficient, necessary in Lithuania in consideration of climate conditions, does not require high maintenance, system installation is fast and simple, the system does not affect train traffic, but rather helps in protecting the most sensitive parts of a switch from snow, especially during a snow storm. During the use of the system, switch blades are not blown out or blown out to a lesser extent. As the electric switch heating is used, the use of electric heating system becomes more efficient because the stock rail maintains heat for a longer period. Furthermore, in consideration of the research carried out, this paper provides the recommendations of the system use.